(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Overweight is defined as abnormal or excessive fat accumulation that presents a risk to health. Once considered a problem only in high-income countries, overweight and obesity are now dramatically on the rise in low and middle-income countries, particularly in urban settings. Overweight and obesity are the fifth greatest risk factors for death worldwide. Due to secondary consequences including obesity, type-2 diabetes mellitus, coronary heart disease, dyslipidemia, etc., the morbidity and mortality of overweight people are rising. Obesity and overweight are primarily caused by an imbalance in energy between calories consumed and calories burned. To maintain balance between the two, the management approach attempts to reduce energy intake while boosting energy expenditure. In Ayurveda, overweight can be correlated to Sthoulya. In this study an intervention along with addition of one dietary intervention was made into the daily routine of subjects. Here yoga is most suitable adaptation of physical activity and Mudgadi kashaya peya is a dietary preparation having Kapha medohara property which can reduce the over gaining weight and presence health.